THE IMPACT OF PEER FEEDBACK ON STUDENTS’ RECOUNT WRITING PERFORMANCE - Sabrina, Fadilatu; Hasanah, Amaliah; Salsabila, Mirrah (Universitas Islam Ogan Komering Ilir Kayuagung, 2025)
This study investigates the impact of peer feedback on students’ achievement in writing recount texts among eleventh-grade students at SMA IBA Palembang. The research aims to determine whether the application of peer feedback can significantly enhance students’ writing performance compared to conventional teaching methods. Employing a quasi-experimental design, the study involved 68 students divided into two groups: the experimental group, which received peer feedback treatment, and the control group, which was instructed using traditional methods. Data were collected through pre-tests and post-tests and analyzed using paired and independent sample t-tests. The findings from the paired t-test revealed a significant improvement in the experimental group (t = -17.985, p = .000), while the control group showed no notable progress. Furthermore, the independent t-test indicated a significant difference between both groups (t = 8.331, p = .000). These results demonstrate that peer feedback is an effective strategy for improving students’ writing performance.